2010
DOI: 10.2139/ssrn.1622714
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Excellence and Extramural Research Grants: Beggars Can't Be Choosers?

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Grant programs by the German Research Foundation (DFG), on the other hand, may support rather basic research agendas as they attract applicants with particular high scientific excellence if measured in publications and citations (Grimpe 2010). Moreover, the result that private sector and public grants are subject to different criteria with respect to research orientation suggests that industry grants offer a additional source of competitive funding for research units that may not be willing or not be able to raise other types of grants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grant programs by the German Research Foundation (DFG), on the other hand, may support rather basic research agendas as they attract applicants with particular high scientific excellence if measured in publications and citations (Grimpe 2010). Moreover, the result that private sector and public grants are subject to different criteria with respect to research orientation suggests that industry grants offer a additional source of competitive funding for research units that may not be willing or not be able to raise other types of grants.…”
Section: Discussionmentioning
confidence: 99%
“…That is which firms collaborate with universities, and what benefits emerge for these firms (Gambardella 1992, Cassiman et al 2008, 2010. Acquisition of scientific research has been shown to be beneficial for firms in many respects ranging from increased productivity of their own R&D efforts (Cockburn and Henderson 1998), to a reduction in labor cost (Stern 2004).…”
Section: Basic Research Applied Research or Best Both?mentioning
confidence: 99%
“…In Germany, as in many other countries, university scientists usually consider several funding types and the funding is often a mix of institutional core-funding and project-based grants (Stephan 1996, Geuna 2001, Schmoch and Schubert 2009. The latter usually stem from either the national government, the States (Bundesländer), grants from the European Union as well as from research foundations, or increasingly from the private sector (see Grimpe 2010). Auranen and Nieminen (2010) study the effects of recent science policies that strengthen the role of competitive funding to increase efficiency of university systems.…”
Section: Sponsored Researchmentioning
confidence: 99%